Famine, migration and war: Comparison of climate change impacts and social responses in North China between the late Ming and late Qing dynasties. (June 2015) - Xiao, Lingbo; Fang, Xiuqi; Zheng, Jingyun; Zhao, Wanyi
The human-climate-ecosystem interactions in the past were valuable for today's human beings who face the challenge of global change. The multi-proxy reconstruction of climate change impacts and social responses and the comparative study between typical periods form an effective tool for elucidating the mechanisms of the interactions. In this paper, with a reconstruction of the proxy series of famine, migration and wars, the most typical social consequences related to climate change and disasters (flood/drought) in North China in 1470–1911 were quantitatively described, and two typical periods of human-climate interaction with similar climate change backgrounds (cold periods of the 'Little Ice Age'), which were the late Ming dynasty (1560–1644) and late Qing dynasty (1780–1911), were selected and compared. It is determined that the climate deterioration (rapid cooling and increasing extreme disasters) in the late 16th and 18th centuries both resulted in severe social consequences characterized by more famine and popular unrest. The differences were that the climatic impacts in the late Ming were much more serious, and interregional migration, which was an effective responsive measure in the late Qing, was not important in the late Ming; they were primarily influenced by three factors based on the analytical framework of the impacts of historical climate change and social responses: (1) climate deterioration in the late Ming was more severe (more rapid cooling and more extreme disasters), (2) social system were more sensitive to climate change in the late Ming because of its mode of agricultural production (especially cropping system and crop species), and (3) the capacity of social response to climate disaster, especially disaster relief and refugee settlement, was considerably greater in the late Qing.